Where do I belong?: finding a Chinese South African Identity in Cyrildene - Lau, Danielle (My University, 2021)
The Chinese South African community is made up of many faces. They camouflage themselves by wearing a variety of different masks that allow them to blend into their surrounding communities. Despite the Chinese community layering themselves with several identities, fitting into South African society has never truly been achieved. The Chinese community is often overlooked, as they choose to hide themselves amongst the shadows of South Africa. Their multi-layered masks are worn as a means of protection due to the Apartheid era. With the exception of a select few, who are not part of the Chinese community, the true identities of the Chinese are hidden in the shadows of South Africa. This thesis will attempt unmask the true identity of the Chinese South African community and understand the migration of the Chinese to South Africa as well as the importance of memory, to create a sense of belonging, for the Chinese South African community
A design project submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Architecture (Professional) July 2021